Impact of different sedation protocols and perioperative procedures on patients admitted to the intensive care unit after maxillofacial tumor surgery of the lower jaw: A retrospective study. Issue 4 (April 2016) - Lebherz-Eichinger, Diana; Tudor, Bianca; Krenn, Claus G.; Roth, Georg A.; Seemann, Rudolf
Abstract: Maxillofacial tumor surgery often necessitates prolonged invasive ventilation to prevent blockage of the respiratory tract. To tolerate ventilation, continuously administered sedatives are recommended. Half-time of sedative or analgesic medication is an important characteristic by which narcotic drugs are chosen, due to the fact that weaning period increases with half-time. The aim of our study was to investigate whether a change in sedation regimen would affect the length of invasive ventilation or intensive care unit stay and medical costs. Additionally, the impact of various surgical procedures was analyzed. Data of 157 patients after mandibular surgery were retrospectively analyzed over 5 years in count regression models. Of those patients, 84 received a sedation regimen with sufentanil and midazolam and 73 with remifentanil and propofol. The impact of the surgical procedures (tracheostomy, tumor resection, neck dissection and length of operation) and the patient age and sex were analyzed with respect to length of ventilation and ICU days. Cost savings were calculated. Our data show that patients receiving remifentanil/propofol had fewer ventilation days (2.5 ± 2.5 versus 6.1 ± 4.6 days, P < 0.001) and were discharged earlier from the intensive care unit than patients receiving sufentanil/midazolam (5.1 ± 3.8 versus 9.2 ± 6.2 days, P < 0.001), leading to calculated cost savings of about 8000 Euro per patient. Length of operation negatively influenced length of ICU stay (P < 0.001). In conclusion, short-acting drugs such as remifentanil/propofol, as well as tracheostoma and shortened surgery duration may reduce the postoperative need for invasive ventilation and length of intensive care unit stay.